Effects of board structure on firm performance: A comparison of Japan and Australia - BONN, Ingrid (Institutional Knowledge at Singapore Management University, 2004)
This article compares the effects of board size, proportion of female directors, proportion of outside directors and average age of directors on firm performance in Japanese and Australian firms. We found that board size and age of directors were negatively associated with the performance of Japanese firms. For Australian firms, outsider ratio and female director ratio were positively associated with performance.